2016
DOI: 10.3390/ph9020018
|View full text |Cite
|
Sign up to set email alerts
|

A Selenium Containing Inhibitor for the Treatment of Hepatocellular Cancer

Abstract: Hepatocellular carcinoma (HCC) is the third most deadly cancer in the world. New treatment strategies are desperately needed due to limited standard therapies. Activation of the Erk, Akt, and STAT3pathways is implicated in the prognosis of HCC. The Se,Se′-1,4-phenylenebis(1,2-ethanediyl) bisisoselenourea (PBISe), is a selenium-containing MAPK and PI3 kinase inhibitor, effectively inhibit tumorigenesis in a variety of experimental models. The aim of our study is to demonstrate the potential role of PBISe in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“… 34 Therefore, the regulation of selenium levels is predicted as a novel therapeutic option for HCC. 35 There are several reports on the anticancer activity of Se‐containing compounds, including organic, inorganic, natural, and synthetic molecules. 36 For instance, a selenium compound, PBISe, was found to be a chemotherapeutic agent in melanoma and human HCC.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Therefore, the regulation of selenium levels is predicted as a novel therapeutic option for HCC. 35 There are several reports on the anticancer activity of Se‐containing compounds, including organic, inorganic, natural, and synthetic molecules. 36 For instance, a selenium compound, PBISe, was found to be a chemotherapeutic agent in melanoma and human HCC.…”
Section: Discussionmentioning
confidence: 99%
“…This fact could explain the different mechanism of action between PBISe and compound 1. Although PBISe inhibited the phosphorylation and total protein levels of Akt in melanoma cells [41], compound 1 did not regulate this protein. We conclude that compound 1 is not effective against either Akt or ERK1/2 and indeed we found that compound 1 inhibits the expression of STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Other preclinical animal models had also been used to study the effect of selenium in liver cancer. Nine or thirteen weeks of sodium selenite (6 p.p.m) supplementation in drinking water prevented the azo dye (3′-MeDAB) hepatocarcinogenesis in male Sprague-Dawley rats [39,40]. Supplementation with sodium selenite or selenomethionine reduces the focal volume and lower GST level in 2-acetylaminofluorene (2-AAF)-induced hepatocarcinogenesis rat model [41][42][43].…”
Section: The Preventive Role Of Selenium In Hcc Tumorigenesismentioning
confidence: 99%
“…Various mechanisms may be involved in the apoptosis induction Selenium in the Prevention and Treatment of Hepatocellular Carcinoma: From Biomedical… DOI: http://dx.doi.org/10.5772/intechopen.88960 role of selenium and selenium-containing inhibitors for HCC. Tagaram et al reported a selenium-containing MAPK and PI3 kinase inhibitor, the Se, Se′-1,4phenylenebis(1,2-ethanediyl) bisisoselenourea (PBISe), possesses anti-proliferative and pro-apoptotic ability in HCC cell lines in vitro and in in vivo in a spontaneous murine HCC model [39]. PBISe promoted apoptosis by inhibiting PI3K, MAPK, and STAT3 signaling in vitro and with significant reduce tumor sizes in vivo (p < 0.007) with a significant reduction in tumor survival marker PCNA and angiogenesis markers Vegf-A, Vegf-R3, and CD34 [39].…”
Section: Anti-proliferative and Apoptosis Induction Role Of Selenium mentioning
confidence: 99%
See 1 more Smart Citation